Minority government in Japan: Limited scope for foreign policy initiatives - Alexandra Sakaki (Stiftung Wissenschaft und Politik (SWP), 2025)
Ishiba Shigeru became prime minister of Japan in October 2024, after unexpectedly winning the leadership of the ruling Liberal Democratic Party (LDP). His long-desired success came with a bitter aftertaste, however. After a poor showing for the LDP in the lower house elections at the end of October 2024, Ishiba now heads a minority government. His party is mired in crisis over the largest political funding scandal in decades, while upper house elections are scheduled for the summer of 2025. Domestic politics will undoubtedly demand Ishiba's attention in the coming months - at a time when the country faces tremendous foreign and security challenges.
Keywords: 320; Japan; Ishiba Shigeru; minority government; Liberal Democratic Party; LDP; Komeito; political funding scandal; Abe Shinzo; Kishida Fumio; Noda Yoshihiko; Constitutional Democratic Party; CDP; Japan Innovation Party; JIP; Democratic Party for the People; DPFP